Prevalence of psychological distress and coping strategies among law enforcement officers - Mohd Nor, Emy Nor Asmieza (2019)
Working in the law enforcement profession can be very demanding on a physical and emotional level. Law enforcement and police officers are often exposed to stressors at work that can lead to depression. This pressure may be due to the nature of this profession in ensuring the protection of life and property through the enforcement of laws and ordinances put in place regardless of any circumstances. Many law enforcement officer experiences stress, anxiety and depression which at a certain level could lead to adverse effect towards individual, organizational, family and people surrounding. In order to overcome these psychological distresses, various coping strategies could be applied by them. The main objective of this study was to identify and measure the level of psychological distress namely stress, anxiety and depression encountered by auxiliary police officers and determined the coping strategies used by them to overcome the stressors. This quantitative study was conducted towards the 650 auxiliary police officer at XYZ Company by conducting a survey using self-report questionnaires. A total of 650 sets of questionnaires were distributed during five different briefing and data collection sessions, 642 questionnaires were collected and only 614 of the collected questionnaires used for the purpose of the study. Quantitative data were analyzed using SPSS software version 23. The results show that amongst psychological distress element, stress has the highest mean score with 2.7, followed by anxiety with 2.14 and depression with 1.93. While for the coping strategy, approach coping mean score was the highest with 2.67 compared to humor/religion (2.51) and avoidance (1.93). On the other hand, the findings revealed that there was no significant relationship determined between stress, anxiety, and depression with avoidance or humor/religion coping strategies. However, there was a significant relationship between psychological distress elements with avoidance coping strategies. The findings of this study make significant contributions to the literature of occupational stress and coping strategies area among auxiliary police population. Instead of that, this study also would be worthy and contributes value to the academic area due to a lack of study conducted among auxiliary police population specifically in Malaysia.